Decreased Gastric Motility in Type II Diabetic Patients. (23rd July 2014) - Chiu, Yi-Chun; Kuo, Ming-Chun; Rayner, Christopher K.; Chen, Jung-Fu; Wu, Keng-Liang; Chou, Yeh-Pin; Tai, Wei-Chen; Hu, Ming-Luen
Abstract : Background . To differentiate gastric motility and sensation between type II diabetic patients and controls and explore different expressions of gastric motility peptides. Methods . Eleven type II diabetic patients and health volunteers of similar age and body mass index were invited. All underwent transabdominal ultrasound for gastric motility and visual analogue scales. Blood samples were taken for glucose and plasma peptides (ghrelin, motilin, and glucacon-like peptides-1) by ELISA method. Results . Gastric emptying was significantly slower in diabetic patients than controls (T50: 46.3 (28.0–52.3) min versus 20.8 (9.6–22.8) min, P ≤ 0.05 ) and less antral contractions in type II diabetic patients were observed ( P = 0 . 02 ) . Fundus dimensions did not differ. There were a trend for less changes in gastrointestinal sensations in type II diabetic patients especially abdomen fullness, hunger, and abdominal discomfort. Although the serum peptides between the two groups were similar a trend for less serum GLP-1in type II diabetic patients was observed ( P = 0 . 098 ) . Conclusion . Type II diabetic patients have delayed gastric emptying and less antral contractions than controls. The observation that there were lower serum GLP-1 in type II diabetic patients could offer a clue to suggest that delayed gastric emptying in diabetic patients is not mainly influenced by GLP-1.